1997
DOI: 10.1084/jem.186.10.1793
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Due to HIV-1 Envelope Interactions with Chemokine Receptors CXCR4 or CCR5

Abstract: Infection with HIV-1 requires expression of CD4 and the chemokine receptors CXCR4 or CCR5 at the target cell surface. Engagement of these receptors by the HIV-1 envelope glycoprotein is essential for membrane fusion, but may additionally activate intracellular signaling pathways. In this study, we demonstrate that chemokines and HIV-1 envelope glycoproteins from both T-tropic and macrophage-tropic strains rapidly induce tyrosine phosphorylation of the protein tyrosine kinase Pyk2. The response requires CXCR4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
273
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(280 citation statements)
references
References 34 publications
5
273
0
2
Order By: Relevance
“…However, little is known about the molecular mechanisms that mediate these functions. We and others have recently shown that CXCR4 can mediate signaling through various components of the focal adhesion complex such as the related adhesion focal tyrosine kinase (RAFTK), also known as Pyk2 or CAK-␤ (23)(24)(25). Furthermore, we also showed that mitogen-activated protein (MAP) kinase and NF-B are activated upon SDF1␣ stimulation (23).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…However, little is known about the molecular mechanisms that mediate these functions. We and others have recently shown that CXCR4 can mediate signaling through various components of the focal adhesion complex such as the related adhesion focal tyrosine kinase (RAFTK), also known as Pyk2 or CAK-␤ (23)(24)(25). Furthermore, we also showed that mitogen-activated protein (MAP) kinase and NF-B are activated upon SDF1␣ stimulation (23).…”
mentioning
confidence: 58%
“…These molecules regulate chemotaxis and cell viability, which are important for various cellular functions such as wound repair, metastasis, inflammation, angiogenesis, and development of lymphoid tissue (55)(56)(57). We and others have recently studied signaling molecules activated by SDF1␣ (23)(24)(25). These studies have shown activation of PI3 kinase and focal adhesion components such as RAFTK/Pyk2, paxillin, and Crk in SDF1␣-induced signaling and in chemotaxis responses of pre-B and T cells (23)(24)(25)27).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, T-tropic infection of monocytes or macrophages requires high threshold levels of CXCR4 on the target cells (Tokunaga et al, 2001). M-and T-tropic HIV gp120s function as agonists for CCR5 and CXCR4, respectively (Davis et al, 1997;Weissman et al, 1997). It is possible that M-tropic HIV gp41-mediated membrane fusion occurs efficiently during the long residence time of occupied CCR5 at the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Another report shows an enhancement of tyrosine phosphorylation of CCR5 and the association of Janus kinase 1/STAT5 with CCR5 after activation by RANTES (53). Furthermore, RANTES can lead to focal adhesion kinase association with CCR5 and Zap70; Lck and Pyk2 are activated after ligand binding (53)(54)(55)(56). How these signals participate in the internalization process or other signaling events is not yet established.…”
Section: Figurementioning
confidence: 99%
“…How these signals participate in the internalization process or other signaling events is not yet established. CCR5 down-modulation could affect signaling elicited by the chemokines or, potentially, the HIV envelope protein (55,57), which may profoundly influence lymphocyte responses because the two crucial signal molecules Lck and Zap70 are affected. It is also important to note that under circumstances in which the TCR is strongly reengaged (for a review, see Ref.…”
Section: Figurementioning
confidence: 99%